Castration methods in crossbred cattle raised on tropical pasture - Moreira, Aline D. [UNESP]; Siqueira, Gustavo R. [UNESP]; Lage, Josiane F.; Benatti, João Marcos B.; Moretti, Matheus H.; Miguel, Giulianna Z.; De Oliveira, Ivanna M.; De Resende, Flávio D. [UNESP] (CSIRO Publishing, 2018)
The aim of this study was to evaluate the effects of castration methods (surgical or immunological-GnRH vaccine) on performance and carcass traits of beef cattle raised until slaughter on tropical pasture. On Day 0, 30 crossbred beef bulls (50% Aberdeen Angus × 50% Nellore) with a bodyweight (BW) of 233 ± 38 kg and age of 8 months were randomly divided into three groups: intact males (INT)-Control, surgically castrated (SUC Day 1), and immunocastrated (IMC Days 1, 84 and 237). Serum testosterone concentrations, scrotal circumference, average daily gain, and ultrasonic backfat depth were evaluated at 42-day intervals (eight evaluations). All animals were slaughtered for the evaluation of carcass traits on Day 336. The GnRH vaccine was efficient in suppressing serum testosterone concentrations (P = 0.02) and scrotal circumference (P < 0.01). No difference in performance was observed between IMC and SUC animals, in which average daily gain was reduced by 14% (P < 0.01) and final BW by 7% (P < 0.01) compared with the INT group. Regardless of the method used, castration improved carcass traits by reducing carcass drip loss during cooling (P = 0.02), by increasing hindquarter percentage (P < 0.01), and by tending to increase the proportion of noble cuts (P = 0.05) compared with the INT group. However, the surgical method was more efficient than the other treatments by increasing fat deposition in the carcass (P < 0.01). Anti-GnRH immunisation in beef cattle raised on tropical pasture can replace surgical castration, but both methods reduce performance. However, in this production system, castration could be an efficient method to add value to the carcass by increasing the hindquarter proportion and fat deposition.
Keywords: anti-GnRH; carcass composition; meat cuts; tropical grass; ultrasound